Treating ‘Septic’ With Enhanced Antibiotics and ‘Arthritis’ by Mitigation of Excessive Inflammation - Kwon, Hyuk-Kwon; Dussik, Christopher M.; Kim, Sang-Hun; Kyriakides, Themis R.; Oh, Irvin; Lee, Francis Y. (Frontiers in Cellular and Infection Microbiology, 2022)
Bacterial infection within the synovial joint, commonly known as septic arthritis, remains a clinical challenge as it presents two concurrent therapeutic goals of reducing bacterial burden and preservation of articular cartilage from destructive host inflammation. We hypothesized that mitigation of MRSA-induced inflammatory signaling could diminish destruction of articular cartilage in the setting of septic arthritis when used in conjunction with antibiotics. Herein, we provide evidence which supports a new therapeutic notion that concurrent antimicrobial therapy to address the ‘septic’ component of the disease with inflammation mitigation to manage the destructive ‘arthritis’ component. We established a murine model to mimic septic knee arthritis, as well as a variety of other inflammatory joint conditions. This murine septic arthritis model, in conjunction with in vitro and ex-vivo models, was utilized to characterize the inflammatory profile seen in active septic arthritis, as well as post-antibiotic treatment, via transcriptomic and histologic studies. Finally, we provided the clinical rationale for a novel therapeutic strategy combining enhanced antibiotic treatment with rifampin and adjuvant immunomodulation to inhibit post-infectious, excess chondrolysis and osteolysis. We identified that septic arthritis secondary to MRSA infection in our murine model led to increased articular cartilage damage compared to various types of inflammatory arthritis. The activation of the pERK1/2 signaling pathway, which is implicated with the mounting of an immune response and generation of inflammation, was increased in intracellular MRSA-infected synovial tissue and persisted despite antibiotic treatment. Trametinib, an inhibitor of ERK signaling through suppression of MEK1/2, alleviated the inflammation produced by the addition of intra-articular, heat-killed MRSA. Further, when combined with vancomycin and rifampin, mitigation of inflammation by pERK1/2 targeting improved outcomes for MRSA septic arthritis by conferring chondroprotection to articular cartilage and diminishing inflammatory osteolysis within bone. Our results support a new therapeutic notion that cell/biofilm-penetrating antibiotics alongside adjuvant mitigation of excessive intra-articular inflammation accomplish distinct therapeutic goals: reduction of bacterial burden and preservation of articular cartilage integrity.